1999
DOI: 10.1063/1.370585
|View full text |Cite
|
Sign up to set email alerts
|

Pt/PbZr x Ti 1−x O 3 interfacial reaction and Schottky barrier formation studied by x-ray photoelectron spectroscopy: Effect of H2 and O2 annealing

Abstract: The Pt/PbZrxTi1−xO3 (PZT) interfacial reaction caused by low-temperature (320 °C) annealing and resulting change in the surface Fermi level position (Schottky barrier height) has been studied by using in vacuo x-ray photoelectron spectroscopy (XPS). A thin (2 nm) Pt layer was deposited on a polycrystalline PZT film and annealed in 0.5-Torr H2 and O2 in a chamber connected to the XPS chamber. For the PZT samples annealed prior to Pt deposition, a small amount of metallic Pb was produced after the Pt deposition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 19 publications
7
26
0
Order By: Relevance
“…It has particularly been observed that the changes may already occur at room temperature. The strong dependence of the barrier height on the chemical state of the interface has also been reported by other groups [22,23]. The effect is not restricted to PZT/Pt but also observed at other oxide/metal interfaces [24,25].…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…It has particularly been observed that the changes may already occur at room temperature. The strong dependence of the barrier height on the chemical state of the interface has also been reported by other groups [22,23]. The effect is not restricted to PZT/Pt but also observed at other oxide/metal interfaces [24,25].…”
Section: Introductionsupporting
confidence: 80%
“…While Pb can dissolve in Pt and therefore remain close to the interface, it is not dissolved in Cu and Ag and hence segregates to the surfaces of these films. The variation of barrier height observed with Pt contacts is accompanied by an increase/decrease of the metallic Pb species [16,22,23]. This suggests that the insensitivity of the barrier height on the metal work function is related [14], respectively, into account, the dipole potential δ can be derived form the discontinuity of the vacuum level E VAC at the interfaces.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…16 Often both effects arise simultaneously to different extent. Potential mechanisms that have been considered during the last two decades are microcracking, 2,22 oxygen vacancy clustering at electrodes, 23 defect cluster growth, 24 suppression of domain nucleation at the electrode interface, 25 charge carrier drift, [26][27][28] breakdown, 28 charge carrier injection, 17,29 depletion regions in the electrodes, 30 injection of protons during processing, 31 ionization of foreign dopants, 32 or ionization even of the host ions. 14 The role of grain boundaries is yet unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In their studies, a prototype Pd/BST/Pt capacitive device was fabricated, and the voltage shift due to the presence of hydrogen at 1000 ppm as high as 4.5 V was measured, which is about 7 times larger than the best value reported in the literature [9][10][11][12][13][14][15][16][17][18][19]. Such voltage shift is believed to originate from the high dielectric constant of amorphous BST thin films, HYDROGEN-SENSITIVE FERROELECTRIC THIN FILM DEVICES 27 which would enhance the dipolar polarization potential at the Pd/BST interface in presence of hydrogen ions. Similarly, a hydrogen-sensitive conduction behavior was also reported in a Pd/amorphous PZT film/Pt capacitive device by Deng et al [22].…”
Section: Introductionmentioning
confidence: 96%